2015
DOI: 10.1007/s00464-015-4447-8
|View full text |Cite
|
Sign up to set email alerts
|

Paraesophageal hernia repair in the emergency setting: is laparoscopy with the addition of a fundoplication the new gold standard?

Abstract: We demonstrate that laparoscopic PEH repair has become accepted in emergent cases. Open PEH repair is often reserved for emergent surgeries and less commonly includes an AR procedure. Laparoscopy with an AR procedure is clearly the standard of care in elective surgery. The decision to perform an open or laparoscopic surgery, with or without adjunctive techniques, may be based more on the physician's comfort with laparoscopic surgery and surgical practices than the patient's condition. Long-term follow-up studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…They demonstrated, however, that patients undergoing emergent surgery via a laparoscopic approach had both decreased mortality (1.47% vs 5.03%, P 4 0.014) and morbidity (8.47% vs 20.64%, P 4 0.014) compared with those undergoing the open approach, supporting the idea that a laparoscopic approach is acceptable in emergent cases. 21 In the present study, patients presenting with obstruction or gangrene undergoing PEH repair were evaluated; of the repairs, 74.1 per cent were performed laparoscopically and 25.9 per cent were performed open. This represents the highest number of laparoscopically completed complex cases evaluated to date for this type of study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated, however, that patients undergoing emergent surgery via a laparoscopic approach had both decreased mortality (1.47% vs 5.03%, P 4 0.014) and morbidity (8.47% vs 20.64%, P 4 0.014) compared with those undergoing the open approach, supporting the idea that a laparoscopic approach is acceptable in emergent cases. 21 In the present study, patients presenting with obstruction or gangrene undergoing PEH repair were evaluated; of the repairs, 74.1 per cent were performed laparoscopically and 25.9 per cent were performed open. This represents the highest number of laparoscopically completed complex cases evaluated to date for this type of study.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,8,11 Whereas multiple studies have demonstrated the benefits of elective laparoscopic PEH repair relative to open repair, including decreased morbidity, mortality, ICU requirements, and length of stay (LOS), [12][13][14][15][16][17][18][19] the number of studies comparing emergent laparoscopic to open repair is limited. 17,20,21 In the present study, we compare the risk factors associated with morbidity and mortality for all patients presenting with complex PEHs undergoing laparoscopic or open repair.…”
mentioning
confidence: 99%
“…Early reports of increased recurrence rates of laparoscopic repair in comparison to the open approach, attributed to less adhesions intraabdominally after laparoscopy, are counterfeited as laparoscopic repair is standardized (25). Laparoscopy is the preferred route in both elective and emergency repair, with a higher though risk of conversion to open in the latter setting (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, quality of life is very good in the rare event of such a procedure needed intraoperatively (33). A partial of even full 3600 fundoplication is an essential part of the operation reducing the recurrence rates and treating the underlying GERD which practically co-exist in most patients, without significant postoperative dysphagia and bloating (27).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding laparoscopic repair of the PEH, Augustin et al 35 determined that the increase in mortality for the emergency surgery group may be related to the degree of deterioration in the patients’ preoperative condition and not to the surgical technique. At the same time, Klinginsmith et al 55 demonstrated that the laparoscopic approach is acceptable in cases of emergency and that the decision about the type of approach should be based more on the surgeon’s experience with the technique than on the patient’s condition. Additionally, 4 studies reported results related to the repair of PEH in the elderly.…”
Section: Discussionmentioning
confidence: 99%